Effect of Peeling Method on The Volatile Flavor of Citrus Fruit. Issue 3 (April 2020) - Wang, Jun; Cheng, Yujiao; Huang, Linhua; Wu, Houjiu; Sun, Rongrong; Li, Guijie
Abstract: Analysis on the volatile flavor of whole peeled citrus fruit with different peeling methods, by solid phase micro extraction-gas chromatography-mass spectrometry (SPME-GC-MS). Totally 50 aromatic components were found, and main components were as follows: limonene (69.32%-78.88%), valencene (8.14%-12.98%), α-pinene (1.01%-1.02%), γ-terpinene (0.27%-0.35%), 3-methyl-butanal (0.75%-1.10%), (E)-2-hexenal (0.47%-0.73%), 1-octanol (0.25%-0.50%), linalool (0.70%-2.16%), ethyl butyrate (0.28%-2.59%), ethyl caproate (5.39%), ethyl acid ethyl ester (0.29%-1.86%), geranylacetone (0.07%-0.25%). The volatile flavor components of the three treatments were 34, 36 and 50, respectively. Enzymatic peeling method was used for detection oxidation of limonene, (E)-2-hexenal flavor. Conventional (artificial) peeling method was used detection oxidation of limonene, (E)-2-hexenal flavor, ethyl hexanoate, hexyl butyrate flavor.